1989
DOI: 10.3109/02844318909004501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Transplantation of Teeth to Simulated Maxillary Alveolar Clefts

Abstract: A total of 14 teeth were transplanted to simulated alveolar clefts in 5 monkeys. Autogenous cancellous bone was grafted to the cleft together with the tooth in ten instances. Healing processes were observed 216 or 271 days postoperatively. Another group of four teeth were transplanted in the cleft areas 133 days after bone grafting. These teeth were observed for 138 days before sacrifice. Radiological and histological findings support previous reports on adverse effects to dental tissues when placed in direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Tooth transplantation recently has become more common in clinical treatment, and significantly higher success rates (>95%) have been reported (Akiyama et al, 1998; Reich, 2008). Previous studies reported encouraging findings for tooth transplantation (Slagsvold and Bjercke, 1978; Stenvik et al, 1989; Andreasen et al, 1990). Autogenous tooth transplantation was applied successfully to the region of upper missing anterior teeth without immunologic problems (Slagsvold and Bjercke, 1978).…”
mentioning
confidence: 90%
“…Tooth transplantation recently has become more common in clinical treatment, and significantly higher success rates (>95%) have been reported (Akiyama et al, 1998; Reich, 2008). Previous studies reported encouraging findings for tooth transplantation (Slagsvold and Bjercke, 1978; Stenvik et al, 1989; Andreasen et al, 1990). Autogenous tooth transplantation was applied successfully to the region of upper missing anterior teeth without immunologic problems (Slagsvold and Bjercke, 1978).…”
mentioning
confidence: 90%
“…In two of those patients, premolar transplantation was performed 1-1.5 years after bone grafting, so this is also possible. Stenvik 5 has published the results from animal experiments and has recommended postponing tooth transplantation, if planned, at least 4 months after bone grafting. Tooth transplantation into freshly grafted bone can lead to root resorption of the donor.…”
mentioning
confidence: 99%
“…Evidence for the success of transplanting premolars, and even molars, to the incisor region has been presented by others (e.g., Natiella et al, 1970;Kristerson and Lagerström, 1991). Premolar transplantation to the site of a cleft is not such a well-known procedure, but results in an animal experimental study by Stenvik et al (1989) and case reports by Hillerup et al (1987) and Hamamoto et al (1998) indicate that this procedure can be successful. Stenvik et al (1989) transplanted 14 teeth to simulated alveolar clefts in five monkeys.…”
Section: Figure 4 a Occlusal X-ray At 8 Years 2 Months B Occlusal mentioning
confidence: 87%
“…Premolar transplantation to the site of a cleft is not such a well-known procedure, but results in an animal experimental study by Stenvik et al (1989) and case reports by Hillerup et al (1987) and Hamamoto et al (1998) indicate that this procedure can be successful. Stenvik et al (1989) transplanted 14 teeth to simulated alveolar clefts in five monkeys. In cases in which the transplantation was done at the same time as the autologous grafts were placed, root resorption and ankylosis occurred to a large extent.…”
Section: Figure 4 a Occlusal X-ray At 8 Years 2 Months B Occlusal mentioning
confidence: 88%
See 1 more Smart Citation